Clinical activity after fingolimod cessation: disease reactivation or rebound?. (10th July 2018) - Frau, J.; Sormani, M. P.; Signori, A.; Realmuto, S.; Baroncini, D.; Annovazzi, P.; Signoriello, E.; Maniscalco, G. T.; La Gioia, S.; Cordioli, C.; Frigeni, B.; Rasia, S.; et al.
Abstract : Background and purpose: There is debate as to whether the apparent rebound after fingolimod discontinuation is related to the discontinuation itself or whether it is due to the natural course of highly active multiple sclerosis (MS). Our aim was to survey the prevalence of severe reactivation and rebound after discontinuation of fingolimod in a cohort of Italian patients with MS. Methods: Patients with relapsing–remitting MS who were treated with fingolimod for at least 6 months and who stopped treatment for reasons that were unrelated to inefficacy were included in the analysis. Results: A total of 100 patients who had discontinued fingolimod were included in the study. Fourteen patients (14%) had a relapse within 3 months after fingolimod discontinuation, and an additional 12 (12%) had a relapse within 6 months. According to this study's criteria, 10 patients (10%) had a severe reactivation. Amongst these patients, five (5%) had a reactivation that was considered to be a rebound. Conclusions: The present study showed that more than 26% of patients are at risk of having a relapse within 6 months after fingolimod discontinuation. Nevertheless, the risk of severe reactivations and rebound is lower than has been previously described. Abstract : Click here to view the accompanying paper in this volume.